2012
DOI: 10.1364/oe.20.00b566
|View full text |Cite
|
Sign up to set email alerts
|

Very long range quasi-Fourier spectroscopy for narrowband lasers

Abstract: The measurement of the spectral broadening, or temporal coherence property of very narrow linewidth lasers is not an easy task, while such a measurement is essential in any interferometric applications of the lasers. The beat note between two assumingly identical lasers only provides the convolutional spectral profile of the two lasers, but not characterizes the single laser. The delayed self-heterodyne interferometer (DSHI) would not be effective for kHz linewidth range because the finite delay cannot realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The theory of the measurement principle has already been presented in [8]: a brief sketch is provided in the following. The measurement system setup ( Fig.…”
Section: Thoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The theory of the measurement principle has already been presented in [8]: a brief sketch is provided in the following. The measurement system setup ( Fig.…”
Section: Thoretical Backgroundmentioning
confidence: 99%
“…Let a q (t)e j 2πν q t and a s (t)e j 2πν s t be the complex amplitudes of the q-th and s-th samples of a laser emission with temporal duration T . If the fluctuation of the beam is ergodic and the observation time T is sufficiently large such that it includes every possible fluctuation, and the sample represents the entire ensemble, then the correlation between the two speckle amplitudes, e q (τ ) and e s (τ ), observed at the delay τ are given by [8] where…”
Section: Thoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not feasible if the delay is finite. Our group recently demonstrated that the degree of coherence (DOC) of a narrow linewidth laser can be accurately characterized with a beam based on Rayleigh speckle analysis using coherent optical frequency domain reflectometry (C-OFDR) with a single sideband (SSB) modulator [6]- [8]. However, a Rayleigh backscattering measurement needs the Manuscript optical amplifier to recover the power loss due to the modulation and connection losses in the SSB modulator.…”
Section: Introductionmentioning
confidence: 99%
“…The novel speckle correlation analysis method is proposed for evaluating the degree of coherence (DOC), by modifying the previously proposed theory [8] and adapting it to the standard phase modulator configuration.…”
Section: Introductionmentioning
confidence: 99%